(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
During these tough economic times, many investors are starting to panic. Since many of these investors are putting their life savings on the line, they want their investments to be safe and smart, yielding positive results both now and in the future. They have lost trust in the stock market and have no idea where to invest their money. In the face of such unsure times, there is a sound solution: invest your money in gold and other precious metals. According to NB/ (National Bullion Investors, LLC), "Gold prices will rise next year as the financial crisis pushes more investors into the precious metal safe haven". For the past ten years, Alan Greenspan, the widely respected former chairman of the US Federal Reserve, has touted the wisdom of investing in gold. He predicted that fiat money would someday be worthless but commented that, "Gold is always accepted. "